1986
DOI: 10.1002/j.1460-2075.1986.tb04530.x
|View full text |Cite
|
Sign up to set email alerts
|

Human basic fibroblast growth factor: nucleotide sequence and genomic organization.

Abstract: Clones encoding the angiogenic endothelial cell mitogen, basic fibroblast growth factor (FGF), have been isolated from human cDNA libraries made from kidney, fetal heart, fetal liver, term placenta, and a breast carcinoma. Basic FGF cDNA clones are present in these libraries at very low levels when compared to the quantity of the growth factor in the tissues. This observation, combined with the fact that several of the clones represent unspliced transcripts, suggests that cytoplasmic basic FGF mRNA is unstable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
1
4

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(207 citation statements)
references
References 34 publications
10
192
1
4
Order By: Relevance
“…bFGF has no typical signal sequence [18,19] suggesting that it may be transported to the outside of the cell via a different pathway from that of normal secretory proteins. The transport and secretion mechanisms are to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF has no typical signal sequence [18,19] suggesting that it may be transported to the outside of the cell via a different pathway from that of normal secretory proteins. The transport and secretion mechanisms are to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…44 However, among the FGF family, bFGF and acidic FGF genes do not encode conventional signal peptide sequences for extracellular FGF release. 3,4,11,22 Consequently, mous cell proliferation mechanisms, such as autocrine, mediated by bFGF/FGFR, at least, in the five cell lines.…”
Section: Effect Of Anti-bfgf Neutralizingmentioning
confidence: 99%
“…At pres-cytoplasm of hepatocellular carcinoma (HCC) cells of 16 of ent, nine members, from FGF-1 to FGF-9, have been identi-56 patients (29%), and another study reported the cultured fied. [1][2][3][4][5][6][7][8][9] The FGF family has been widely distributed in normal HCC cell line, SK Hep-1, can produce bFGF in vitro. 31 Normal and/or tumor tissues, and they are known to take various hepatocytes do not express the bFGF receptor, FGFR-1, while important roles, e.g., in angiogenesis, tissue regeneration, a hepatoblastoma cell line (HepG2) has been reported to exwound healing, and embryonic development.…”
mentioning
confidence: 99%
“…FGF1 and 2 have been implicated in tumor development and malignant progression (for review see Rifkin and Moscatelli, 1989;Courlier et al, 1997). FGF1 and 2 lack a classic signal peptide (Abraham et al, 1986;Jaye et al, 1986), implying that they are not secreted by the classical secretion pathway. There is evidence that FGF1 and 2 are exported from the cell and subsequently act as autocrine or paracrine factors (Vlodavski et al, 1982;Sato and Rifkin, 1988).…”
Section: Introductionmentioning
confidence: 99%